Association of the characteristics of the blood metabolome and gut microbiome with the outcome of methotrexate therapy in psoriasis - Qiu, Qinwei; Deng, Jingwen; Deng, Hao; Yao, Danni; Yan, Yuhong; Ye, Shuyan; Shang, Xiaoxiao; Deng, Yusheng; Han, Lijuan; Zheng, Guangjuan; Roy, Bhaskar; Chen, Yang; et al. (Frontiers in Immunology, 2022)
Metabolic status and gut microecology are implicated in psoriasis. Methotrexate (MTX) is usually the first line for this disease. However, the relationship between MTX and host metabolic status and the gut microbiota is unclear. This study aimed to characterize the features of blood metabolome and gut microbiome in patients with psoriasis after treatment with MTX. Serum and stool samples were collected from 15 patients with psoriasis. Untargeted liquid chromatography-mass spectrometry and metagenomics sequencing were applied to profile the blood metabolome and gut microbiome, respectively. We found that the response to MTX varied according to metabolomic and metagenomic features at baseline; for example, patients who had high levels of serum nutrient molecular and more enriched gut microbiota had a poor response. After 16 weeks of MTX, we observed a reduction in microbial activity pathways, and patients with a good response showed more microbial activity and less biosynthesis of serum fatty acid. We also found an association between the serum metabolome and the gut microbiome before intervention with MTX. Carbohydrate metabolism, transporter systems, and protein synthesis within microbes were associated with host metabolic clusters of lipids, benzenoids, and organic acids. These findings suggest that the metabolic status of the blood and the gut microbiome are both involved in the effectiveness of MTX in psoriasis, and that inhibition of symbiotic intestinal microbiota may be one of the mechanisms of action of MTX. Prospective studies in larger sample sizes are needed to confirm these findings.